Whimsical - Gershon, Max (Northridge Review, 2025)
Print. Exhibited as part of Words and Pictures, 2025 in Manzanita Gallery from March 17 to April 18, 2025. Coördinated and Installed by Michele Hatfield, Curated by Erik Mark Sandberg and Sean Pessin.